PENGARUH KEAKTIFAN BELAJAR MATEMATIKA TERHADAP HASIL BELAJAR MATEMATIKA SISWA DI MI NURUL FALAH KUTOREJO - Jamilatun Nurjannah; Agung Purwono (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2024)
Mathematics Learning Activity is all activities that are physical and non-physical students in the process of optimal teaching and learning activities so as to create a classroom atmosphere when the Mathematics learning process becomes conducive. As for the indicators of activeness in learning Mathematics consists of 8 indicators, namely: Activeness of Seeing, Activeness of Speaking, Activeness of Listening, Activeness of Writing, Activeness of Drawing, Motor Activeness, Mental Activeness, Emotional Activeness. Some indicators of activeness in learning Mathematics will affect students' Mathematics learning outcomes. The main purpose of this study is to determine the influence of the variable of mathematics learning activity (X) on the variable of mathematics learning outcomes (Y). This research is a research with a quantitative approach using a causal comparative research design. The sample in this study was 173 students and located at MI Nurul Falah Kutorejo. The data collection techniques used are in the form of questionnaire instruments and documentation activities. Using data analysis, namely, including: test validity, reliability, normality, linearity, and hypothesis. Based on the calculation of the hypothesis test, a signification value of 0.008 < 0.05 was found, so for the conclusion, Ha was accepted and Ho was rejected. The results of the hypothesis test in this study show that the variable of mathematics learning activity affects the mathematics learning outcomes of students at MI Nurul Falah Kutorejo. It was also obtained for the R square result of 0.041 which stated that the magnitude of the influence of the variable of mathematics learning activity (X) on mathematics learning outcomes (Y) was 4%. The other influence, namely 96% (100%-4%) is influenced by other variables that are not studied